Development of Smart Box Learning Media to Improve Students’ Learning Outcomes on the Topic of Pancasila as the State Foundation in Grade II - Siti Nuril Hidayatus Shofiyah (PGMI, STAI Miftahul Ula Nganjuk, 2025)
The development of Smart Box learning media for Grade II students at Madrasah Ibtidaiyah Al-Karim was based on several challenges encountered in the learning process, namely the failure to achieve learning objectives, particularly in the Civic Education subject on the topic of Pancasila as the foundation of the state. In addition, the limited availability of learning media due to inadequate facilities and the continued use of assignment-based learning methods led teachers to utilize the surrounding environment as learning media. The objectives of this study are as follows: (1) to develop visual learning media in the form of a Smart Box for the topic of Pancasila as the foundation of the state for Grade II students at Madrasah Ibtidaiyah Al-Karim; (2) to describe the validity of the developed Smart Box learning media on the topic of Pancasila as the foundation of the state for Grade II students at Madrasah Ibtidaiyah Al-Karim; and (3) to describe the results of the trial implementation of the Smart Box learning media on the topic of Pancasila as the foundation of the state for Grade II students at Madrasah Ibtidaiyah Al-Karim Senggowar Gondang. The research method employed in this study is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) using a Research and Development (R&D) research design. The subjects of this study were 20 Grade II students at Madrasah Ibtidaiyah Al-Karim. Data collection methods included observation, interviews, and questionnaires. Observations were conducted to examine teaching and learning activities and to analyze students’ characteristics. Interviews were conducted with the Grade II teacher to identify the needs of both students and teachers in the learning process, while questionnaires were distributed to material experts, media experts, teachers, and students. Overall, the research results show that the media expert validation test achieved a percentage score of 98%, while the material expert validation test reached 96%. Student responses to the media reached 92% in the first trial stage and increased to 98% in the second trial stage, indicating a “very good” qualification in which students were able to understand the material and use the media effectively. Meanwhile, the teacher’s response to the media reached 90%. Therefore, the Smart Box learning media is considered highly feasible for use as an instructional medium.